A systematic investigation of forensic hair decontamination procedures and their limitations. Issue 10 (2nd September 2019) - Mantinieks, Dylan; Wright, Paul; Di Rago, Matthew; Gerostamoulos, Dimitri
Abstract: The effectiveness of decontamination procedures used for the removal of external drug contamination in forensic hair analysis is an ongoing debate. This investigation evaluated wash methods complying with Society of Hair Testing (SoHT) guidelines and their capacity to remove cocaine (COC) and methamphetamine (MA) from artificially contaminated hair. The most effective decontamination method was determined using a systematic approach, involving (1) an initial washing solvent screen, (2) optimization of wash duration, (3) comparison of sequential wash methods, and (4) reanalysis of clinical hair samples. For analysis, hair was subjected to micro‐pulverized methanolic extraction prior to quantitation by ultra‐high performance liquid chromatography−tandem mass spectrometry (UHPLC−MS/MS). Methanol (MeOH) and 0.1 M phosphate buffer (pH 6) were the most effective organic and aqueous solvents, respectively, removing 28%–38% of COC and 16%–31% of MA. Wash durations longer than 30–60 minutes did not remove additional amounts, and a more efficient sequential wash method was subsequently developed. Despite this, the interpretation of reportable results relative to the SoHT cut‐off levels was unchanged for most clinical hair samples reanalyzed after washing by agitation for 30 minutes with MeOH. These findings highlight the inability of decontamination solvents to completely remove external COC and MA contamination from hair, including wash methods adhering to SoHT guidelines. Abstract : A systematic investigation of hair decontamination procedures adhering to Society of Hair Testing recommendations failed to remove external cocaine and methamphetamine contamination. As such, preparative solvent washing in forensic hair analysis should focus on maximizing the recovery and detectability of metabolites.